2023
DOI: 10.3390/cancers15123207
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Management of Clear Cell Renal Cell Carcinoma: Novel Biomarkers and Targeted Therapies

Valentina Schiavoni,
Roberto Campagna,
Valentina Pozzi
et al.

Abstract: Renal cell carcinoma (RCC) belongs to a heterogenous cancer group arising from renal tubular epithelial cells. Among RCC subtypes, clear cell renal cell carcinoma (ccRCC) is the most common variant, characterized by high aggressiveness, invasiveness and metastatic potential, features that lead to poor prognosis and high mortality rate. In addition, diagnosis of kidney cancer is incidental in the majority of cases, and this results in a late diagnosis, when the stage of the disease is advanced and the tumor has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 183 publications
0
17
0
Order By: Relevance
“…Pharmacologic inhibition of PARP is the primary therapeutic strategy for BReast CAncer gene ( BRCA ) mutant ovarian cancer, but most patients carry wild-type BRCA1/2 and show no clinical benefits from PARP inhibitors [ 72 , 73 ]. The TP53 gene encodes the p53 tumor suppressor protein and is the most frequently mutated gene in human cancer, leading to the survival of cancer cells, ineffective therapeutic responses and unfavorable prognoses [ 74 ]. Importantly, it has been reported that p53 can repress SLC7A11 expression, which favors ferroptosis [ 75 ].…”
Section: Slc7a11 Modulation By Natural and Synthetic Compounds In Ova...mentioning
confidence: 99%
“…Pharmacologic inhibition of PARP is the primary therapeutic strategy for BReast CAncer gene ( BRCA ) mutant ovarian cancer, but most patients carry wild-type BRCA1/2 and show no clinical benefits from PARP inhibitors [ 72 , 73 ]. The TP53 gene encodes the p53 tumor suppressor protein and is the most frequently mutated gene in human cancer, leading to the survival of cancer cells, ineffective therapeutic responses and unfavorable prognoses [ 74 ]. Importantly, it has been reported that p53 can repress SLC7A11 expression, which favors ferroptosis [ 75 ].…”
Section: Slc7a11 Modulation By Natural and Synthetic Compounds In Ova...mentioning
confidence: 99%
“…Each year, it is estimated that more than 225,000 individuals are diagnosed with this condition, resulting in over 100,000 deaths annually [1]. Despite progress in early detection and therapeutic strategies that have improved earlystage diagnosis and patient survival, ccRCC continues to exhibit high rates of occurrence and mortality [2]. In the absence of treatment, ccRCC is highly aggressive, leading to invasion and metastasis, and the survival rate drops to around 10% five years after metastasis has occurred [2].…”
Section: Introductionmentioning
confidence: 99%
“…Despite progress in early detection and therapeutic strategies that have improved earlystage diagnosis and patient survival, ccRCC continues to exhibit high rates of occurrence and mortality [2]. In the absence of treatment, ccRCC is highly aggressive, leading to invasion and metastasis, and the survival rate drops to around 10% five years after metastasis has occurred [2]. While surgical intervention is pivotal in treating ccRCC, close to 40% of individuals undergo recurrence after surgery [3], posing a significant burden on both patients and their relatives [4].…”
Section: Introductionmentioning
confidence: 99%
“…Tivozanib is a tyrosine kinase inhibitor and promising anticancer agent due to its ability to inhibit the vascular endothelial growth factor receptor (VEGFR), which is critical in the growth of blood vessels that supply nutrients to tumors [ 17 , 18 ]. Tivozanib has primarily been used to treat advanced renal cell carcinoma (RCC), and studies have shown that it effectively impedes tumor blood vessel growth and potentially reduces tumor growth rates [ 19 ]. Surprisingly, there is a notable lack of research on its pharmacological effects on OSCC cells; hence, there is a critical need for comprehensive investigations in this area.…”
Section: Introductionmentioning
confidence: 99%